Contamination when collecting trace evidence—An issue more relevant than ever?. (December 2015) - Pickrahn, Ines; Kreindl, Gabriele; Müller, Eva; Dunkelmann, Bettina; Zahrer, Waltraud; Cemper-Kiesslich, Jan; Neuhuber, Franz
Abstract: With the development of more sensitive DNA amplification and STR typing kits, the chance of detecting minute contamination of trace material increases. At the same time, possible ways of detecting unwanted contamination of crime scene samples were also enhanced. To estimate the contamination rate of biological traces nationwide, we continued a study from 2010 that compares the number of analyzed crime scene samples with the number of detected contamination incidents within our laboratory. The results of this study illustrate the importance of reference profiles, especially of crime scene investigators, and the advantage of database assisted profile alignment in cases of mixtures.